Kinetics Study of Cd2+ and Zn2+ Metal Ion Adsorption Using Zeolite 4A - Ervin Tri Suryandari; M.A. Zulfikar; M. Nasir (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2017)
Cd (II) and Zn (II) are examples of heavy metal contaminants in waters that cause serious problems because of their toxicity. Therefore, it is necessary to take effective way to remove heavy metal ions from waters. Adsorption method is widely used because it has several advantages, namely high efficiency, easy handling, reusable, inexpensive, and many choices of materials that are used as adsorbent. One effective adsorbent used is a zeolite because it has high selectivity. This study aims to determine the kinetic model suitable for the process of Cd2+ and Zn2+ metal ion adsorption using Zeolite 4A as an adsorbent. The study was conducted by varying the contact time (10, 15, 30, 45, 60, 90, 120 and 180 minutes). The results showed that the Cd2+ adsorption process followed the pseudo-second-order model with a value of k = 0.205 g mg-1 min-1, R2 = 0.998, while the Zn2+ adsorption process followed the pseudo-second-order model with a value of k = 0.087 g mg-1 min-1, R2 = 0.995.. ©2017 JNSMR UIN Walisongo. All rights reserved